Range detection approach in interactive virtual heritage walkthrough - Sunar, Mohd. Shahrizal; Zin, A. M.; Sembok, T. M. T. (IEEE Computer Society, 2006)
Exploring virtual world will give a memorable experience to the users. Generally, they are expecting smooth navigation with high quality image drawn into their eyes. Nevertheless, when the virtual world is growing simultaneously with the number of objects, the navigation will be detained. Yet, the frame rates can become unacceptable. In this paper, we present and examine range detection approach for view frustum culling to effectively speed-up the interactive virtual heritage project namely Ancient Malacca Virtual Walkthrough. Normal six plane view frustum culling approach use the plane equation to test whether objects is within the visible region. However, range detection approach is different with normal six plane view frustum. It is based on camera referential point and tests the objects if they are in the viewing range. The results show that this approach is able to increase the rendering performance of the virtual walkthrough without sacrificing the visual quality.